2018
DOI: 10.17239/l1esll-2018.18.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Student work and the multimodal challenge: A mixed methods study of students’ productive work in L1, science and mathematics

Abstract: Students' productive work constitutes an essential part of the various learning activities students are involved in while in school. However, empirical research on students' productive work in schools is quite sparse, and thus, we only know little about what kind of products the students make in different subjects, and how they relate to learning. This article presents a mixed methods study on students' productive work in the subjects L1, science and mathematics in primary and lower secondary school in Denmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is a commonly accepted notion that language teaching and learning benefit from TALL. TALL offers students, most of whom are "born digital," opportunities to move beyond traditional and rigid barriers of traditional face-to-face teaching and learning (Bremholm, Hansen, & Slot, 2018). Equitable access to multiple learning modes evens the learning grounds for each student who might otherwise have less contact with the target language from traditional classes.…”
Section: Impact Of Technology On Language Teaching and On Teachersmentioning
confidence: 99%
“…It is a commonly accepted notion that language teaching and learning benefit from TALL. TALL offers students, most of whom are "born digital," opportunities to move beyond traditional and rigid barriers of traditional face-to-face teaching and learning (Bremholm, Hansen, & Slot, 2018). Equitable access to multiple learning modes evens the learning grounds for each student who might otherwise have less contact with the target language from traditional classes.…”
Section: Impact Of Technology On Language Teaching and On Teachersmentioning
confidence: 99%
“…Only a few studies have been undertaken of Danish L1 writing at lower secondary level, and for the most part those did not focus particularly on writing in the literature classroom (Bremholm et al, 2018;Christensen et al, 2014). One notable exception is the work of Krogh and Piekut (2015), who suggested that personal experiences are valued alongside more creative text formats or "productive analysis" in the year 9 Danish L1 literature classroom.…”
Section: Writing In the L1 Literature Classroommentioning
confidence: 99%
“…The result of this focus has been that sociolinguistic and ethnographic approaches have dominated the field. However, forwarded particularly, of course, by the appearance of new digital methods, but also by the fact that written language still remains the main mode of non-verbal communication in both school and everyday life (Biber & Egbert, 2018;Brandt, 2014;Bremholm et al, 2018), we are now slowly seeing a resurgence of written language itself as an important object of study in writing research.…”
Section: Educational Writing Researchmentioning
confidence: 99%